ECONOMIC ORDER QUANTITY (EOQ) ON RAW MATERIAL INVENTORY OF PT. PANEN EMBUN KEMAKMURAN - Eni Suasri; Widya Astuti Alam Sur; Ines Saraswati Machfiroh; Muhammad Abdianor Nasrullah (Faculty of Economic and Business Universitas STIKUBANK, 2022)
This study aims to determine the frequency of purchasing raw materials for Cup 220 ml and Straw optimally using the Economic Order Quantity (EOQ) method at PT. Panen Embun Kemakmuran. The type of data used is quantitative data, with the research method being qualitative. The results showed that the optimal purchase frequency for the 220 ml Cup type is 3 times and Straw 8 times in one year. The number of safety stock that must be owned by the company for 220 ml Cup is 1.503.277 and Straw 1.264.144 Pcs. The company must place a reorder or reorder point for 220 ml Cups when supplies reach 1.931.320 Pcs and Straw 1.695.596 Pcs. The total cost of inventory if PT. Panen Embun Kemakmuran using the EOQ method is IDR 139,806,429, the company can save for 220 ml Cup raw materials of IDR 56.862.105 and Straw of IDR 341.704 or overall savings of IDR 57.203.809.